EFFECT OF ENALAPRIL AND METFORMIN ON OXIDATIVE STRESS IN NEWLY DIAGNOSED TYPE 2 DIABETES MELLITUS AND HYPERTENSIVE PATIENTS - AT, SATHIYA VINOTHA; PALANIMUTHU, SENTHILKUMARAN (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The present study was aimed to find out the impact of Enalapril and Metformin on oxidative stress (OS) in newly diagnosed diabetes mellitus and hypertensive patients. Methods: A free radical production was measured by lipid peroxidation and antioxidants like catalase, reduced glutathione, glutathione s-transferase, and superoxide dismutase were measured using ultraviolet spectrophotometer. Results: There was a significant decrease in free radical production and a significant increase in antioxidant enzymes in both the treatment groups. Conclusion: Enalapril and metformin combination in diabetic patients has a more significant effect on OS than metformin alone. This combination also has a significant effect on OS in diabetes and hypertension coexisting patients. Keywords: Oxidative stress, Enalapril, Metformin, Antioxidants.